2018
DOI: 10.1177/0363546517751660
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Hamstring Tendon Regeneration and Functional Recovery After Harvesting: A Prospective Follow-up Study

Abstract: Hamstring tendon regeneration occurs less frequently in older patients and in smokers. However, absence of regenerated tendons does not seem to cause a loss of function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The diagnosis of semitendinosus tendon snapping may be based on the history and findings from a physical examination, 8 but a complete examination may be possible only after anesthesia has been induced and the tourniquet has been inflated. Tendon regeneration may be observed in 67.1% of patients who have undergone an autograft hamstring anterior cruciate ligament reconstruction at 2-year follow-up, 15 and, in our opinion, MRI may show only semitendinosus tendon thickening in patients with a previously harvested tendon for anterior cruciate ligament reconstruction (Fig 4).
Fig 4Magnetic resonance imaging showing semitendinosus thickening in a previously harvested tendon for anterior cruciate ligament reconstruction.
…”
Section: Discussionmentioning
confidence: 68%
“…The diagnosis of semitendinosus tendon snapping may be based on the history and findings from a physical examination, 8 but a complete examination may be possible only after anesthesia has been induced and the tourniquet has been inflated. Tendon regeneration may be observed in 67.1% of patients who have undergone an autograft hamstring anterior cruciate ligament reconstruction at 2-year follow-up, 15 and, in our opinion, MRI may show only semitendinosus tendon thickening in patients with a previously harvested tendon for anterior cruciate ligament reconstruction (Fig 4).
Fig 4Magnetic resonance imaging showing semitendinosus thickening in a previously harvested tendon for anterior cruciate ligament reconstruction.
…”
Section: Discussionmentioning
confidence: 68%
“…Many studies have reported that hamstring tendons regenerate after harvesting. 5,19,26,29,32,33 In a recent systematic review, semitendinosus and gracilis tendons regenerated in at least 70% of patients after harvesting. 32 Ferretti et al 10 and Eriksson et al 9 used open biopsies and demonstrated that not only the scar tissue but also the real tendon regenerated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the GRA and ST tendons offer a tissue volume that is much greater than that which the upper limb can provide, which explains their varied use for ligament surgery of the upper limb [17] [9]. Finally, these tendons regrow between 60 and 80% of cases in the months following their removal [18]. Passing through the remaining cuff 100%…”
Section: Discussionmentioning
confidence: 99%